Utilizzo della scheda di premappatura dei pericoli nel comparto delle ceramiche artistiche / Use of premapping of risks data sheet in artistic ceramics industries - Di Leone, G.; Nicoletti, S.; Monopoli et al., L. (La Medicina del Lavoro, 2011)
«Use of premapping of risks data sheet in artistic ceramics industries». Background: In 2006 there were more than 10,000 people working in artistic ceramics industries in Italy. The jobs in these industries that attracted most attention were work at the potter’s wheel and decorating. Objectives: To test the premapping of risks data sheet in these enterprises. Methods: We tested the data sheet in 3 craft industries: one was mainly artistic, one had a semi-industrial setting and in the third jobs were non-specific. Results: In the semi-industrial craft industry the risks for potter’s wheel workers were higher due to the repetitive movements required and to work organization aimed at achieving maximum productivity. Conclusions: the premapping of risks data sheet is a very sensitive tool. It can sometimes overestimate the risks, but in this way identifies situations that call for more in-depth analysis using tools that comply with international standards.